KUALITAS PELAYANAN : FAKTOR-FAKTOR YANG MEMPENGARUHI DAN DAMPAKNYA PADA NILAI PELANGGAN (Studi Pada PT. Angkasa Pura I (Persero) Kantor Cabang Bandara Ahmad Yani Semarang) - Novanto, Herdanu Sri (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2009)
The passenger growth in the Ahmad Yani Airport Semarang increases each year, but it is not followed with the the growth of optimal service quality. This phenomena occurs because PT. Angkasa Pura I (Persero) Ahmad Yani Airport Semarang does not care about the importance of the customer value especially for the services in the passenger station and the parking area. Based on the problem, the aim of this research is to examine affecting factors and the impact to customer value..To achieve the aim of this research, the model which explores in this research use four variables. The variables are information technology quality, service facility design quality, service quality and customer value. Data about the variables was collected by using questionnaires that was distributed to 100 visitors of Ahmad Yani Airport Semarang. Then the data is analyzed under the Structural Equation Modeling (SEM) Method.The result shows that the test over the five hypotheses can be statistically proven in which the service quality is proven to have a positive and significant impact to customer value, information technology quality is proven to have a positive and significant effect to customer value, information technology quality is proven to have a positive and significant effect to service quality, service facility design quality is proven to have a positive and significant effect to customer value, and service facility design quality is proven to have a positive and significant effect to service quality.